The Effect of Adding Cassava Peel to Liquid Organic Fertilizer on Kale - Izar, Kharis Maulana; Chusnah, Miftachul (AGARICUS: Advances Agriculture Science & Farming, 2025)
The utilization of organic waste as a raw material for liquid organic fertilizer (LOF) is an environmentally friendly alternative to support sustainable agriculture. Cassava peels contain simple carbohydrates and nutrients that can improve the quality of LOF and promote plant growth. This study aimed to determine the effect of adding cassava peels to vegetable waste-based LOF on the growth of water spinach (Ipomoea aquatica). The experiment was conducted using a Completely Randomized Design (CRD) with four treatments: P0 (control), P1 (LOF + 10% cassava peels), P2 (LOF + 20% cassava peels), and P3 (LOF + 30% cassava peels), each replicated three times. Parameters observed included plant height, leaf number, leaf length, root length, fresh weight, and soil pH. Data were analyzed using ANOVA, followed by LSD test at a 5% significance level. Results showed that adding cassava peels improved plant growth, with P3 giving the best numerical results for most parameters, such as plant height (31.8 cm), leaf length (6.78 cm), and soil pH (8.20). Although not all parameters were significantly different, the overall trend indicated that LOF enriched with cassava peels could improve fertilizer quality and support the vegetative growth of water spinach. Keywords: liquid organic fertilizer; cassava peels; experiment; water spinach; plant growth.